THE ROLE OF NET FINANCING CASH FLOWS IN THE GROWTH OF BANKING INSTITUTIONS (AN APPLIED STUDY OF A GROUP OF COMMERCIAL BANKS LISTED IN THE IRAQ STOCK EXCHANGE) - M. M. Salam idan Marzouk (Scholar Express Journals, 2023)
The growth of banking institutions is of the main pillars that represent the strength of the banking sector, which enhances the quality and diversity of banking services provided to customers, which is considered one of the constants of market competition among commercial banks. and This topic has been selected as a cognitive Starting point and a goal for the researcher To introduce the concept of net financing cash flows and its impact on the growth of banking institutions. As well as identifying the nature and concept of the growth of banking institutions and their impact on increasing the profitability of the bank commercial and increasing its ability to compete in the labor market. The researcher proceeds from the hypothesis that there is a correlation and effect between the net financing cash flows and the growth of banking institutions and tries to prove it using quantitative analysis of statistical methods (simple linear correlation and simple linear regression). By selecting a set of financial indicators, which were represented by the indicators of measuring the independent variable (net financing cash flows) over the years of research, as were the indicators of the dependent variable (growth of banking institutions), namely (the ratio of deposits to capital - the profitability ratio - the liquidity ratio) . As these indicators are part of a group of factors that have a significant impact on measuring the development and growth of the banking institution and the adoption of two commercial banks (Bank of Baghdad and the Investment United Bank) as an intended sample for research and a time series extending over five years from (2016 to 2020), The researcher reached a set of conclusions, the most important of which was the existence of a weak and insignificant correlation and impact relationship between the independent variable and the dependent variable, as well as there was a set of recommendations, including the need for commercial banks to show greater interest in the banking investment policy of the existing resources that help growth and development, since these resources are mostly Available and lack of proper investment
Keywords: net financing cash flows; growth of banking institutions; liquidity